The Washington manual hematology and oncology subspecialty consult - Cashen, Amanda F.; Van Tine, Brian A. (Washington manual subspecialty consult series., 2016)
"The Washington Manual Hematology and Oncology Subspecialty Consult, 4th Edition, provides quick access to the essential information needed to evaluate a patient on a subspecialty consult service. This edition offers state-of-the-art content, including coverage of new anti-cancer drugs and new biomarkers and therapeutic targets. Ideal for fellows, residents, and medical students rotating on hematology and oncology subspecialty services, the manual is also useful as a first-line resource for internists and other primary care providers"--Publisher's description.